Fillet welding of austenitic stainless steel using the double channel shielding gas method with cored wire - Mert, Tolga; Gultekin, Nurullah; Karaaslan, Ahmet (CARL HANSER VERLAG, 2015)
X2CrNi189 austenitic stainless steel material with web and flange thicknesses of 10 mm was welded by the conventional GMAW and double channel shielding gas method to form double fillet T-joints. The difference between these two methods were characterized by measurements of mean welding parameters, Vickers hardness profiles, molten and HAZ areas of the joints as well as by thermal camera temperature measurements. According to the results, higher mean current intensity but lower mean arc voltage along with higher heat input was obtained using the double channel shielding gas method. There was no significant difference observed in Vickers hardness between the two methods. Moreover, mean filler metal molten area values were higher with double channel shielding gas method, which depicted that this method increased productivity.
Keywords: Welding; double channel torch; stainless steel; cored wire; T-joint; Materials Science